In Vitro Antiproliferative Activity in Plants of the Genus Tabebuia: A Systematic Review - Laura Mosquera-Morales; Lina Marcela Orozco; Luz Angela Veloza; Juan Carlos Sepúlveda-Arias (Molecules)
The use of plant extracts and the compounds isolated from them for the treatment of cancer is an area of active research, given their therapeutic potential. This work focused on evaluating the literature related to the antiproliferative activity of extracts obtained from plants of the genus Tabebuia and molecules isolated in vitro or in vivo. For the search, MeSH and DECS terms were employed in the PubMed, Scopus, and SciELO databases. Research has shown that plant extracts derived from plants of the genus Tabebuia exhibit potential applications in the search for new molecules with antiproliferative activity. Among the isolated molecules, the most evaluated correspond to β-lapachone (naphthoquinone); however, molecules with antiproliferative potential belonging to groups such as iridoids, flavonoids, quinones, furanonaphthoquinones, triterpenes, and polysaccharides have also been isolated and reported. Additionally, synthesized molecules have been evaluated on the basis of the modifications made to the structures of molecules isolated from the plant extracts to increase their activity, aiming to develop more potent antitumor agents for future clinical use.